Validity and reliability scientific literacy-based physics assessment instrument on atomic nucleus and radioactivity material - Ladika Zuhrotul Wardi; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Universitas PGRI Kanjuruhan Malang, 2025)
Indonesia has a low level of scientific literacy, so it is necessary to make efforts for teachers to develop appropriate assessments or assessment instruments. In this research, a physics assessment instrument will be developed based on scientific literacy on atomic nuclei and radioactivity with the aim that the resulting instruments are good and feasible to use. This research is a type of development research. The feasibility analysis of the assessment instruments in this study included validity, reliability, level of difficulty, and differentiability. The assessment instrument will be validated by three expert lecturers as validators. The test subjects in this study were 35 first-year students of the Physics Education Study Program, at Surabaya State University. Based on the results of data analysis, it can be concluded that the scientific literacy-based physics assessment instrument on atomic nuclei and radioactivity developed has a logical validity value for the content domain of 100% in the very valid category, the construction domain of 92.85% in the valid category, and the language by 85.71% with very valid category. As for the empirical validity value, 50% of the questions are in the valid category and 50% are in the invalid category. The reliability value is 0.492 which means reliable. Furthermore, for the difficulty level of the items, 20% of the questions were in the easy category, 65% of the questions in the moderate category, and 15% of the questions in the difficult category. As well as for the discriminating power of the items, 10% of the items were in the good category, 35% were in the sufficient category, and 55% were in the less category.